Children's diets, pesticide uptake, and implications for risk assessment: An Israeli case study. (January 2016) - Freeman, Shirra; Kaufman-Shriqui, Vered; Berman, Tamar; Varsano, Rina; Shahar, Danit R.; Manor, Orly
Abstract: The presence of pesticides in the Israeli food supply is well documented but little is known about the risks posed by children's diets for potential exposures. We investigated potential exposures to food-borne pesticides in a sample of 301 urban Israeli children (2008–10). Data from a food frequency questionnaire, 24 hour food recall, and Israel's national pesticide monitoring program were used to estimate uptake factors for 26 compounds in 27 fruits and vegetables. A pilot risk assessment was performed and the findings were compared with the Israel Ministry of Health's 2012 pesticide risk assessment for the general population. The surveyed children had higher potential exposures than the general population for over one third of the compounds, and uptake factors exceeded the Acceptable Daily Intake in ten compounds. Methamidophos, exceeded the ADI at the 25th percentile and fenamiphos, iprodione, and oxydemethon methyl, exceeded the ADI at the 50 percentile. ADIs for several compounds were exceeded even though the residues detected were below the statutory limit. Improved monitoring, enforcement, and revision of the Maximum Residue Limit for certain food/pesticide pairs are indicated as is the need to incorporate data on children's actual food consumption in national risk assessments. Highlights: Pesticide monitoring and dietary surveys were used to estimate potential exposure. Children were shown to have greater uptake than adults in 12 of 26 compounds. Uptake exceeded the acceptable daily intake (ADI) in 10 compounds. Using actual dietary data in pesticide risk assessment is recommended.